The Discourse of the Body in the Novel "The Accusing Finger," a Woman... whose Heart is a Cloud, by Djamila Zanir - Bounechada, Nabila (Journal of Human Sciences, 2020)
Female writing caused a revolution in the context of modern Arab narratives, as it did not remain in the crucible of isolation, the specific pattern, and the drawn roles, but rather it announced its great presence in the current literary canon through the act of writing which began to search through its effectiveness for its discursive specificity related to its feminine nature and its vision, and her philosophy of female pain whose features and identity were defined in a time of self-fragmentation, and the power of cultural oppression and intellectual rape. The novel "Fingers of Accusation" is a model of the female physical discourse in all its details, movement and struggle with the other. According to a vision that reflects the ideological legacies of Arab societies in particular, the novel is a response to this reality by exposing anti-women attitudes.